Operation Sovereign Borders: The Very Real Risk of Refoulement of Refugees - Dechent, Susanna (Legal Service Bulletin Co-Operative Ltd, 2014)
This article examines the main features of ‘The Coalition’s Operation Sovereign Borders Policy’, released in July 2013. The author explains the international legal obligations Australia owes to asylum seekers and refugees within jurisdiction, specifically the prohibition on refoulement under the Convention Relating to the Status of Refugees and its 1967 Protocol. The article then analyses how the Coalition’s deterrent measures, together with key sections of the oft-amended Migration Act 1958 (Cth), compare with Australia’s international law obligations. The article concludes that refoulement of refugees is likely to result, unless Australia succeeds in securing comprehensive co-operation of multiple sovereign states in the Asia-Pacific region.